(untitled) (Research, Society and Development, 2025)
The growing demand for water, driven by changes in consumption patterns, population explosion and economic growth, makes it essential to analyze the quality of this vital resource. This study aims to evaluate the physical-chemical and microbiological quality of the water used in three public fountains located in the Núcleo Velha Marabá, in the neighborhoods of Centro and Francisco Coelho (Cabelo Seco), in Marabá - PA, in order to analyze whether they meet the potability standards required by current legislation. The physical-chemical analyses revealed variations in the parameters at all points, with emphasis on the high presence of ammonia at point 2 (Fountain at NEI Deodoro Mendonça School), indicating pollution by nearby sewage. Nitrate concentrations above the established limits were also observed, mainly at the same point, suggesting sewage contamination. In the microbiological analysis, total coliforms were detected at points 1 (Fountain at Praça Francisco Coelho) and 2 (Fountain at Hospital Materno Infantil), not meeting the established standards. The concentration of nitrates above the limit established by the current Ordinance was found in the three samples analyzed, indicating possible contamination by sewage discharge, in addition to indicating remote pollution, since nitrates are end products of nitrogen oxidation. The quality of the water in the fountains analyzed in Velha Marabá is compromised by sewage contamination, evidenced by the presence of ammonia, nitrates and coliforms. This reinforces the need for monitoring, adequate treatment and public policies to ensure the population’s water security.